Evaluation Method of Floor Heave Damage Degree and a Case Study in Zaoquan Coal Mine, China - Ai Chen; Qing Ma; Xuesheng Liu (Shock and Vibration, 2021)
With the continuous increase of mining depth and complex mining geological conditions, the mileage of roadways in underground engineering such as coal mine is increasing year by year. Complex conditions lead to different floor heave failure laws, and the control technology and strategy should be changed accordingly. How to evaluate the damage degree of floor heave under different conditions has become an urgent problem. Firstly, this paper makes a statistical analysis on the main evaluation indexes of the damage degree of roadway floor heave. Then, the fuzzy comprehensive clustering method is used to establish the classification method of floor heave damage degree, taking the floor heave amount, floor rock fragmentation degree, coal pillar size, buried depth, and floor lithology as evaluation indexes. The damage degree of floor heave can be divided into five types: light type, obvious type, severe type, destructive type, and extremely severe type. Finally, the rationality and accuracy of the method are verified by the measured value and evaluation value of No. 130203 roadway in the Zaoquan coal mine. The results can provide reference for the evaluation of the damage degree of the floor rock in similar condition mine and provide guidance for the design of the support and stability control of the failure of the roadway floor heave.